2015
DOI: 10.1111/bph.13225
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐(1–7) administration benefits cardiac, renal and progenitor cell function in db/db mice

Abstract: Background and Purpose Diabetic patients are at an increased risk of cardiovascular disease, in part due to inflammation and oxidative stress. These two pathological mechanisms also affect other organs and cells including the kidneys and progenitor cells. Angiotensin‐(1–7) [Ang‐(1–7)] has previously been shown to counterbalance pathological effects of angiotensin II, including inflammation and oxidative stress. The aim of this study was to investigate the effects of short‐term (2 weeks) Ang‐(1–7) treatment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…), Losartan potassium (0.4 mg/kg, i.p. ), PD 123319 (0.4 mg/kg, i.p), 44 vehicle (0.9% saline, i.p. ), or a combination of Ang-(1-7) and each antagonist.…”
Section: Methodsmentioning
confidence: 99%
“…), Losartan potassium (0.4 mg/kg, i.p. ), PD 123319 (0.4 mg/kg, i.p), 44 vehicle (0.9% saline, i.p. ), or a combination of Ang-(1-7) and each antagonist.…”
Section: Methodsmentioning
confidence: 99%
“…Elegant studies have shown that bone marrow oxidative stress in mouse models of diabetes by Ang-(1-7) in diabetic bone marrow and increased levels of NO/cGMP levels (Mordwinkin et al, 2012;Papinska et al, 2015). CD34 cells derived from diabetic individuals have shown increased ROS levels that were normalized by Ang-(1-7), which was associated with increased NO levels (Jarajapu et al, 2013).…”
Section: Role Of No In Vasculogenic Functions Of Ang-(1-7)mentioning
confidence: 99%
“…Similar findings were observed when dysfunctional diabetic cells were overexpressed with lentiviral ACE2 gene transfer in a mouse model of hindlimb ischemia . Pharmacological targeting of ACE2 or MasR has been proven to be successful in experimental models for diabetic wound healing and cardiopulmonary disorders, and the reparative end-points were associated with increased vascular regenerative capacity (Mordwinkin et al, 2012;Shenoy et al, 2013;Singh et al, 2014;Papinska et al, 2015;Vasam et al, 2017). Despite the shorter biological half-life, Ang-(1-7) administration has been shown to be effective even in nanomolar doses in a wide range of experimental models.…”
Section: The Promise Of Ace2/ang-(1-7)/masr Axis In Regenerative Pharmentioning
confidence: 99%
“…Additionally, an improvement in physiological heart function and cardiomyocyte hypertrophy was observed in Ang-(1–7)-treated mice (Papinska et al 2015). Alamandine is similar to Ang-(1–7) and differs only by the presence of an alanine residue in place of an aspartate residue at the amino end.…”
Section: Discussionmentioning
confidence: 99%